"All of a sudden we noticed a difference at home too": parents' perception of a parent-focused early communication and AAC intervention for toddlers. (2nd July 2020) - Fäldt, Anna; Fabian, Helena; Thunberg, Gunilla; Lucas, Steven
Abstract: Augmentative and alternative communication (AAC) can enhance children's communication and is recommended to be introduced as soon as problems are identified. The aim of this interview study was to investigate how parents perceive the ComAlong Toddler intervention offered to parents of children with communication difficulties early in the diagnostic process. ComAlong Toddler consists of a 5-session, group-based, parental course, and two home visits that focus on responsive communication, enhanced milieu teaching, and multimodal AAC. Interviews were conducted 1 year after the intervention with 16 parents who had attended ComAlong Toddler. The data were analyzed through qualitative content analysis, resulting in four categories: (a) Development for us and the child, (b) acquiring useful tools, (c) useful learning strategies, and (d) benefits and challenges regarding intervention structure. Findings suggest that parents of toddlers with language or communication disorders learned and appreciated responsive communication and enhanced milieu teaching. All had used multimodal AAC and described its benefits. Parents emphasized the value of learning from other parents as well as from a speech-language pathologist who engaged with their child in the home environment. Parents suggest an enhanced family focus as a potential improvement.